Work Life Balance dalam Manajemen Sumber Daya Manusia Modern: Perspektif Lembaga Pendidikan Islam dan Pesantren - Avifahtur Nur Rohma; Baidi Baidi (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study discusses the importance of Work Life Balance (WLB) for teachers and educational staff in Islamic boarding schools (pesantren). The boarding system requires educators to be active around the clock, which often leads to stress, emotional exhaustion, and decreased teaching motivation. Findings indicate that implementing welfare-based management—such as work schedule rotation, proportional workload distribution, and social support from leaders—has a positive impact on teachers’ motivation and psychological well-being. Spiritual values such as sincerity (ikhlas) and reliance on God (tawakal) also strengthen their psychological resilience. Therefore, the application of WLB in pesantren should be grounded in humane policies and Islamic values to achieve harmony between work productivity, worship, and personal life. Pesantren can thus serve as a model of holistic human resource management that integrates both worldly and spiritual well-being.